The Dynamics of Development : Innovation and Reallocation - Buera, Francisco J.; Fattal-Jaef, Roberto N. (World Bank, Washington, DC, 2018)
This paper proposes a quantitative model of endogenous firm dynamics to study growth acceleration episodes triggered by reforms. It finds that reversals of entry distortions lead to persistent growth in TFP and declining average firm size, as in the experience of successful post-communist transitions. Removing idiosyncratic distortions results in a more protracted path of TFP and a rising average firm size, as in non-communist growth accelerations. When calibrating the reforms to China’s liberalization, the model accounts for one-third of the observed growth in TFP, while matching the dynamics of average firm size and income inequality..